2015
DOI: 10.1002/chem.201405538
|View full text |Cite
|
Sign up to set email alerts
|

A Non‐Invasive NMR Method Based on Histidine Imidazoles to Analyze the pH‐Modulation of Protein–Nucleic Acid Interfaces

Abstract: A useful (2) J(N-H) coupling-based NMR spectroscopic approach is proposed to unveil, at the molecular level, the contribution of the imidazole groups of histidines from RNA/DNA-binding proteins on the modulation of binding to nucleic acids by pH. Such protonation/deprotonation events have been monitored on the single His96 located at the second RNA/DNA recognition motif (RRM2) of T-cell intracellular antigen-1 (TIA-1) protein. The pKa values of the His96 ionizable groups were substantially higher in the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…Hydrogen bond interactions were observed that help to explain the preferential binding of U-rich or T-rich oligonucleotides. In particular, an interaction between His96 and the third thymine base provided structural verification of a previous observation that the pKa of this histidine sidechain is impacted by RNA binding (28,29). We further probed this using NMR and observed increased signal intensities of the sidechain N-H signals upon DNA binding, again consistent with the formation of an oligonucleotide interaction with His96.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Hydrogen bond interactions were observed that help to explain the preferential binding of U-rich or T-rich oligonucleotides. In particular, an interaction between His96 and the third thymine base provided structural verification of a previous observation that the pKa of this histidine sidechain is impacted by RNA binding (28,29). We further probed this using NMR and observed increased signal intensities of the sidechain N-H signals upon DNA binding, again consistent with the formation of an oligonucleotide interaction with His96.…”
Section: Discussionsupporting
confidence: 70%
“…This interaction likely explains the previously reported rise in p K a value of His96 that occurs upon oligonucleotide binding by TIA-1 RRM2 (28). The direct hydrogen bonding of His96 Nδ 1 would be expected to increase the nucleophilicity of the Nε 2 atom of the imidazole and thus raise the p K a .…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Eukaryotic RRMs are often found as multiple copies within a protein, and together with other protein domains, they confer different affinity and specificity for the RNA sequences . RRMs are also found in prokaryotes, where they tend to occur as single domains in small proteins, typically around 100 amino acids in length (Pfam ID PF0076 and InterPro ID IPR000504 ).…”
Section: Discussionmentioning
confidence: 99%